ANALISIS ANTRIAN PASIEN INSTALASI RAWAT JALAN POLIKLINIK LANTAI 1 DAN 2 RSUD CENGKARENG, JAKARTA - Nadeak, Sanitoria; Sugito, Sugito; Suparti, Suparti (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2016)
The queue process associates with the arrival of the costumers of a service facility, waiting in a queue line when all waiters are busy, and finally left the facility after being served. Queuing phenomena can be found in public service facilities, such as in District General Hospital (RSUD) Cengkareng. The length of the registration procedure, consultation services for physicians, and waiting time for the pharmacy services, can influence the satisfaction of the patients of Outpatient Installation of RSUD Cengkareng. Therefore, it is necessary to have an appropriate queue model to get an effective service, balanced and efficient, that can reduce the long queues and waiting time. From the analysis, the queue model for the registration of the Workers Social Security Agency (BPJS) patient is (M /M/6):(GD/∞/∞) with the number of server is 6 counters and for the non BPJS patients is (M/M/2):(GD/∞/∞) with the number of server is 2 counters. The queue model for the psychiatrist clinic and anesthetic is (M/M/1):(GD/∞/∞) with the number of server is 1 counter. The queue model for the other Polyclinic is (M/M/c):(GD/∞/∞) with the number of server depends on the clinic itself.Keywords: Queue, Outpatient Installation, District General Hospital (RSUD) Cengkareng